(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2015)
Objective: Annually, a significant number of electricity-induced deaths (electrocution) occurs throughout the world. According to the report by the Iranian Legal Medicine Organization (LMO), 6750 cases of electrocution were referred to the autopsy halls of LMO during 2004–2014. In addition to death, a large number of non-fatal electrical accidents are associated with severe and sometimes irreparable injuries such as extensive burns, skeletal fractures, loss of vision and hearing, brain damages and paralytic dysfunctions. Methods: This study was carried out on 124 cases of electrocution referred to the autopsy hall of Tehran Office of LMO. Clinical and autopsy findings entered in related forms and analysed by statistic methods. Results: The victims were mostly low educated, young (21–30 years old) male workers, who were electrocuted by accidental exposure to electricity through urban power lines. In most cases the accident had occurred in residential settings and an electric mark was evident in 88.7% of cases and frequently on the victims’ hands. The most common findings in autopsy were bleeding and pulmonary congestion. Conclusion: Preventive measures such as educational programs on the usage of electrical instruments, sufficient safety measures in dangerous environments like industrial plants, workshops, power transfer stations, and high-voltage posts, and increasing the level of awareness in this regard among industrial workers, electricians and others who deal with electrical current.